Transcatheter correction of atrial septal defects in children of various age groups, its results, and effects on the right atrium remodelling - R. S. Tarasov; E. S. Kartashyan; V. I. Ganyukov; I. N. Sizova (Российский кардиологический журнал, 2013)
Aim. The issue of safety and effectiveness of endovascular correction of atrial septal defects (ASD) in children aged 0–3 years remains controversial, due to a range of technical challenges and inadequate knowledge on the right atrium remodeling consequences in children across age groups. We analysed the in-hospital, 30-day, and long-term (12 months) outcomes of transcatheter correction of secundum ASD and occluder implantation in 89 children. Material and methods. All patients were divided into two groups: Group 1 (n=49) – younger children (mean age 1,7±0,6 years) who were operated before the age of 3; and Group 2 (n=40) – older children (mean age 6,2±3,2 years), who underwent the surgery after the age of 3. In both groups, no in-hospital or long-term (12 months) adverse effects, such as death, occluder migration, or the need for open surgery, were registered. Results. By Day 30 after the surgery, both groups demonstrated a consistent, significant reduction in mean size of right atrium, which persisted for the next 12  months (p<0,05). Conclusion. In children aged 0–3 years, endovascular correction of ASD is safe and effective. It is also beneficial in terms of right atrium remodelling effects, both in younger children (mean age 1,7±0,6 years) and in older children (mean age 6,2±3,2 years).